Development of Illustrated Books on the Theme of Coral Reef Conservation to Improve the Character and Conservation Ethics of Elementary School Students - Muhammad Iqbal (Journal of Asian Primary Education (JoAPE), 2026)
Indonesia's coral reefs face a serious threat of degradation due to destructive human activities such as bombing, potash and ship anchoring and climate change, while marine conservation education at the primary school level is still very limited. This research aims to develop a picture animation book with the theme of coral reef conservation as a valid, practical, and effective learning medium to improve general knowledge, specific knowledge, character, and conservation ethics of grade IV elementary school students. The development model used is ADDIE (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of 32 grade IV students in two elementary schools of State 2 Labuhan Kananga in the coastal area of Moyo Satonda National Park. Data was collected using validation sheets of material experts, media experts, teacher and student response questionnaires, as well as pre-tests and post-tests. The results of the validation of material experts obtained an average score of 89.6% (very feasible) and the validation of media experts 91.2% (very feasible). The teacher's response reached 93.4% and the student's response was 88.7%. The effectiveness test using N-Gain showed an increase in general knowledge by 0.63 (moderate) and specific knowledge by 0.48 (moderate). The score of conservation character increased by 31.4% and conservation ethics increased by 27.8% based on observation rubrics. This study concludes that the illustrated book with the theme of coral reef conservation developed is feasible and shows a moderate but meaningful effect as a learning medium for marine environmental conservation in elementary schools